2015
DOI: 10.1088/0953-8984/27/9/095604
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, magnetic, and transport properties of the isotypic aluminides SmT2Al10(T= Fe, Ru)

Abstract: We report the results of a comprehensive physical and magnetic property study of the new isotypic aluminides SmT₂Al₁₀ (T = Fe, Ru). These two compounds are members of a rare-earth based system which has become an exemplary case study of the interplay of magnetism and correlated electron phenomena. SmFe₂Al₁₀ and SmRu₂Al₁₀ are found to order in a putative antiferromagnetic spin arrangement at T(N) = 14.5 K and 12.5 K, respectively. Moreover, SmRu₂Al₁₀ shows a further phase transition at T(SR) = 5 K which is like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
2
7
1
Order By: Relevance
“…Figure 4 shows the temperature dependence of magnetic specific heat and entropy at zero field, which almost reproduces the data reported in Ref. 24. The large λ-type anomaly in C mag (T ) at T N reflects the magnetic ordering.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 4 shows the temperature dependence of magnetic specific heat and entropy at zero field, which almost reproduces the data reported in Ref. 24. The large λ-type anomaly in C mag (T ) at T N reflects the magnetic ordering.…”
Section: Resultssupporting
confidence: 84%
“…Basic properties of this compound using a polycrystalline sample has been reported recently. 24 We report the results of electrical resistivity, magnetic susceptibility, and specific heat measurements using a single crystalline sample. It is shown that successive phase transitions take place at T N =12.3 K and at T M =5.6 K, which confirms the previous report.…”
Section: Introductionmentioning
confidence: 99%
“…The speciality of samarium arises from the perpetual competition between its two stable valence states: nonmagnetic Sm 2+ and a magnetic Sm 3+ , which is stabilized in many solids by the formation of spatially homogenous non-integral intermediate valence Sm 2.x+ . Experimental examples of samarium containing intermediate valence compounds include the extensively studied SmB 6 [5,6]; high-pressure golden-phases of SmS, SmSe and SmTe [7]; ambient SmO [8]; SmFe 2 Al 10 [9]; Sm 2.75 C 60 [10]; and elemental samarium metal itself [11]. The intermediate valence state of samarium can be understood as an intra-atomic promotion of 4f electrons to 5d bands, going from Sm 2+ (4f 6 5d 0 ) to Sm 3+ (4f 5 5d 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The χ(T ) behavior is qualitatively different from other Sm-based systems like SmFe 2 Al 10 where strong valence fluctuations have been reported [46]. However a simple Curie-Weiss description was not suitable for Sm 3 Ru 4 Ge 13 and van Vleck terms in the total magnetic susceptibility were required to fit the data.…”
Section: Discussionmentioning
confidence: 68%
“…The high temperature magnetic susceptibility of Sm compounds can have significant contributions from van Vleck terms [45]. The fact that valence fluctuations and crystal field effect contributions play a role in the magnetic susceptibility of Sm-based intermetallics is shown in the case of SmFe 2 Al 10 and SmRu 2 Al 10 [46]. The 1/χ(T ) plot of SmFe 2 Al 10 showed a broad plateau-like region signifying the underlying valence fluctuation of the Sm 3+ ions; however, such a feature is absent in the present Sm-compound.…”
Section: Magnetizationmentioning
confidence: 99%